Development of Science and Technology in Sports Through Test and Measurement Tools Shoulder and Wrist Android Based - Ilmi Arifin; Amir Supriadi; Ibrahim Sembiring (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study is to produce Android -based shoulder and wrist. This research was conducted on students of the Faculty of Sports Sciences and North Sumatra PON athletes in December 2022. Types of research used in this study were development research with Research & Development (R&D) research designs from Borg and Gall. This research was conducted with 9 research stages, namely, (1) Research and Information Collecting, (2) Planning, (3) Developing Preminary Form of Product, (4) Preminary Field Testing, (5) Main Product Revision, (6) Main Field Testing, (7) Operational Product Revision, (8) Operational Field Testing, (9) Final Product Revision. The population in this study by using students of the Faculty of Sports Science and the North Sumatra Taekwondo Pelatda athlete. The technique of picking up using purposive sampling with a trial of phase I of 20 FIK students and the phase II trial of 30 athletes in North Sumatra Taekwondo Pelatda. Furthermore, from the trial of phase I, totaling 20 people showed 96% with very feasible criteria, then from the phase II trial of 30 North Sumatra Taekwondo Pelatda athletes showed 91% with a very decent category. From the results of research /feasibility tests conducted by test experts and measurements, IT experts and sports academics show 96% with a very feasible category, so that it can be used. On the basis of the data obtained, the development of Android -based shoulder and wrist test equipment is declared feasible to be developed as a test tool and measurement of shoulder muscle and wrist.